Value of Flat-detector Computed Tomography Angiography with Intravenous Contrast Media Injection in the Evaluation and Treatment of Acutely Ruptured Aneurysms of the AcomA complex: A Single Center Experience in 15 Cases - Rösch, Julie; Lang, Stefan; Gölitz, Philipp; Kallmünzer, Bernd; Roessler, Karl; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2018)
Objective To illustrate the added value of flat-detector computed tomography angiography with intravenous contrast media injection (intravenous FDCTA) in the evaluation of complex A1/A2/AcomA aneurysms. Patients and Methods We retrospectively reviewed 15patients with ruptured aneurysms. In each patient, an intravenous FDCTA was performed and its diagnostic value investigated. Results In all patients, FDCTA contributed relevant additional information concerning the anatomy of the A1/A2/AcomA complex and the relationship of the aneurysm neck to these vascular structures, which could not be gained by 2D- and 3D-DSA, and changed the management in 33% of the patients (5 out of 15). In an additional 5cases, knowledge of the detailed anatomy was helpful to plan the exact stent position. Conclusion In case of complex A1/A2/AcomA aneurysms, intravenous FDCTA is an effective option to visualize the exact location of the aneurysm neck and the relationship between the aneurysm and the adjacent vessels. Thus, it is of significant added value in the precise planning of atherapeutic strategy.
EVALuna2:34934